OPTIMIZATION OF TOURIST ATTRACTION DEVELOPMENT (CASE STUDY: TUAN KENTANG TOURIST VILLAGE PALEMBANG) - Kaiman; Elly Malihah; Rini Andari (Journal Hotspot, 2025)
Rural tourism is a tourism activity where the tourist experience is related to various nature-based activities, agriculture, and lifestyle in the countryside. South Sumatra itself has at least 123 tourist villages spread across several districts and cities. There are many potential tourist villages in the city of Palembang, one of which is the tuan kentang village. Tuan kentang village is located on Jl. Aiptu a wahab kec. Seberang Ulu I kota Palembang.Tuan kentang is known as the "village of fabrics" because there are more than a hundred traditional fabric craftsmen living in this area. The focus of this research is to find out how to optimize the development of tourist attractions in the tuan kentang villages. The methodology used in this study is a qualitative method with a case study approach. Tuan kentang tourism village has considerable potential to become a tourist destination that has attraction and uniqueness. Of the many potentials in this village area, it is hoped that the government and the community can work together in improving and developing this area. The role of the community is needed to develop the potential in this village, especially in anticipating the existing obstacles, including the active role of the community in helping to promote this village and fostering a sense of ownership and awareness of this tourist village. Then it is hoped that the local government of Palembang city can support everything in an effort to optimize the development of tourist attractions in this Tuan kentang tourist village.